Peptide‐functionalized double network hydrogel with compressible shape memory effect for intervertebral disc regeneration - Chia‐Yu Ho; Chen‐Chie Wang; Tsung‐Chiao Wu; Chen‐Hsiang Kuan; Yu‐Chung Liu; Tzu‐Wei Wang (Wiley, 2023)
Abstract As a prominent approach to treat intervertebral disc (IVD) degeneration, disc transplantation still falls short to fully reconstruct and restore the function of native IVD. Here, we introduce an IVD scaffold consists of a cellulose‐alginate double network hydrogel‐based annulus fibrosus (AF) and a cellulose hydrogel‐based nucleus pulposus (NP). This scaffold mimics native IVD structure and controls the delivery of Growth Differentiation Factor‐5 (GDF‐5), which induces differentiation of endogenous mesenchymal stem cells (MSCs). In addition, this IVD scaffold has modifications on MSC homing peptide and RGD peptide which facilitate the recruitment of MSCs to injured area and enhances their cell adhesion property. The benefits of this double network hydrogel are high compressibility, shape memory effect, and mechanical strength comparable to native IVD. In vivo animal study demonstrates successful reconstruction of injured IVD including both AF and NP. These findings suggest that this double network hydrogel can serve as a promising approach to IVD regeneration with other potential biomedical applications.